Analisis Efektivitas Proses Produksi Kopi Menggunakan Metode Value Stream Mapping (VSM) pada Agroindustri PDP Sumber Wadung - Fatimatuzzahro, Fatimatuzzahro; Ramli, Ani Sulistiyawati; Mudakir, Imam; Asyiah, Iis Nur (Politeknik Negeri Lampung, 2026)
Coffee is one of Indonesia’s leading agricultural commodities, contributing significantly to the national economy and export performance. The efficiency of post-harvest processes plays a crucial role in ensuring green bean quality and maintaining industry competitiveness. This study aims to evaluate the efficiency of the coffee production process at PDP Sumber Wadung Agroindustry using the Value Stream Mapping (VSM) approach. The research was conducted in November 2025 at PDP Sumber Wadung, Silo District, Jember Regency, employing a descriptive-analytical method through observation, interviews, and documentation to collect data related to process flow, machine capacity, cycle time, and the distribution of value-added (VA) and non-value-added (NVA) activities. The Current State Map showed that the proportion of VA activities reached around 60%, while NVA activities remained around 40%, with the main bottlenecks identified in the mason dryer and manual sorting stages. The dominant types of waste included waiting, transportation, motion, overprocessing, and defects. Based on these findings, a Future State Map was developed that integrates improvement strategies, including layout redesign, parallel processing, process standardization, implementation of 5S, Kaizen, and production leveling (Heijunka). The simulation results show an increase in VA activity to more than 80%, a decrease in NVA activity to 18–20%, and a reduction in total lead time from 28–30 hours to 20–22 hours per batch. The results of this study indicate that applying lean manufacturing principles through VSM can improve production flow, reduce waste, and support continuous quality improvement in green coffee bean processing.